CE-16 The prevention, screening, and treatment of congenital heart block from neonatal lupus: a survey of provider practices. (31st August 2016) - Clowse, Megan E B; Eudy, Amanda; Bermas, Bonnie; Chakravarty, Eliza; Sammaritano, Lisa R; Chambers, Christina
Abstract : Background: There are presently no official guidelines about the prevention, screening, and treatment of congenital heart block (CHB) due to maternal Ro antibodies. The objective of this study was to survey an international sample of providers to determine their current practices. Materials and methods: A survey was designed by the organising committee of the 9th International Conference of Reproduction, Pregnancy and Rheumatic Diseases. It was sent to 330 people who were prior or current attendees of the conference or authors of recent publications or abstracts at ACR 2012, 2013, or 2014 on rheumatic diseases and pregnancy. Missing demographic information led to exclusion from analysis (n = 11). Results: There were 48 respondents. Most (55%) follow >15 pregnancies in rheumatic patients per year, and 33% were practicing rheumatologists for >15 years. Most were university-based physicians (88%) and from North America (42%) or Europe (42%). Screening: In anti-Ro/SSA positive women, 80% recommended serial fetal ECHOs, with most starting at gestational week 16 (59%) and stopping at week 28 (25%), although the time to stop varied widely. For women without a prior infant with neonatal lupus, respondents recommend every other week (44%) or weekly (28%) fetal ECHOs. For women with a prior infant with neonatal lupus, 80% recommend weekly fetal ECHOs. Prevention: Hydroxychloroquine was recommended by 67% of respondents to prevent CHB and most would start pre-pregnancy (62%). Treatment: Respondents were asked about medications for varying degrees of CHB in a 20-week pregnant, anti-Ro and La positive SLE patient. Respondents recommended dexamethasone (53%) or HCQ (43%) for 1 st degree HB; dexamethasone (88%) for 2 nd degree HB; and dexamethasone (55%), IVIg (33%), or no therapy (27%) for complete HB. When dexamethasone was started for 2nd degree CHB, 58% would stop dexamethasone if it progressed to complete heart block, 47% would stop if heart block disappeared, and 24% would stop if the 2nd degree CHB remained. Conclusions: Despite the absence of official guidelines, many physicians with a clinical focus on pregnancy and rheumatic disease have developed similar patterns in the screening, prevention, and treatment of CHB. These include serial fetal ECHOs, preventive HCQ, and treatment of early heart block with dexamethasone. These practices are not uniform, however, and have not been formally tested in prospective trials. The next step in this field must include testing of these approaches to identify the most cost effective and efficacious plan for these pregnancies.